Genome of Acanthamoeba castellanii highlights extensive lateral gene transfer and early evolution of tyrosine kinase signaling - Clarke, Michael; Lohan, Amanda J; Liu, Bernard; Lagkouvardos, Ilias; Roy, Scott; Zafar, Nikhat; Bertelli, Claire; Schilde, Christina; Kianianmomeni, Arash; Bürglin, Thomas R; Frech, Christian; Turcotte, Bernard; et al. (Genome biology, 2013)
Background The Amoebozoa constitute one of the primary divisions of eukaryotes, encompassing taxa of both biomedical and evolutionary importance, yet its genomic diversity remains largely unsampled. Here we present an analysis of a whole genome assembly of Acanthamoeba castellanii ( Ac ) the first representative from a solitary free-living amoebozoan. Results Ac encodes 15,455 compact intron-rich genes, a significant number of which are predicted to have arisen through inter-kingdom lateral gene transfer (LGT). A majority of the LGT candidates have undergone a substantial degree of intronization and Ac appears to have incorporated them into established transcriptional programs. Ac manifests a complex signaling and cell communication repertoire, including a complete tyrosine kinase signaling toolkit and a comparable diversity of predicted extracellular receptors to that found in the facultatively multicellular dictyostelids. An important environmental host of a diverse range of bacteria and viruses, Ac utilizes a diverse repertoire of predicted pattern recognition receptors, many with predicted orthologous functions in the innate immune systems of higher organisms. Conclusions Our analysis highlights the important role of LGT in the biology of Ac and in the diversification of microbial eukaryotes. The early evolution of a key signaling facility implicated in the evolution of metazoan multicellularity strongly argues for its emergence early in the Unikont lineage. Overall, the availability of an Ac genome should aid in deciphering the biology of the Amoebozoa and facilitate functional genomic studies in this important model organism and environmental host.